The approximation function of bridge deck vibration derived from the measured eigenmodes - Sokol, Milan; Komorníková, Magdaléna; Bacigál, Tomáš; Rodríguez, Miguel X. (Zielona Góra: Uniwersytet Zielonogórski)
This article deals with a method of how to acquire approximate displacement vibration functions. Input values are discrete, experimentally obtained mode shapes. A new improved approximation method based on the modal vibrations of the deck is derived using the least-squares method. An alternative approach to be employed in this paper is to approximate the displacement vibration function by a sum of sine functions whose periodicity is determined by spectral analysis adapted for non-uniformly sampled data and where the parameters of scale and phase are estimated as usual by the least-squares method.
Keywords: eigenmode approximation; eigenmode derivatives; regression spline; spectral analysis; distributed parameter system